Settlement Policy of Criminal Actions which Performed by Children through Penal Mediation - Feri Satria Wicaksana Effendy; Arpangi Arpangi (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2021)
One form of progressive law in the Juvenile Criminal Justice System is the existence of penal mediation. The benchmark for the positive implications of penal mediation as a force is expected to encourage efforts to alleviate various issues that have been identified. Thus, the conditions for implementing penal mediation as the embodiment of Pancasila values in order to support the rule of law in the context of national development are expected to be truly realized. The problem in this research is how is the technical implementation of penal mediation in Indonesia? and How is the Penal Mediation Process at the stage of Investigation, Prosecution and Examination in Court Sessions. The method used in this study is normative juridical, which relates to the policy of resolving crimes committed by children through penal mediation. Penal mediation in the Juvenile Criminal Justice System Act is called Diversion. In accordance with Article 7 paragraph (1) of Act No. 11 of 2012 concerning the Juvenile Justice System, at the level of investigation, prosecution and examination of children's cases in district courts, diversion must be sought, based on a Restorative justice approach.